Budaya Populer dan Estetika Baru melalui Pesona Make Up dan Kostum dalam Film Asterix at the Olympic Games - Sandi Tramiaji Junior; Autar Abdillah; Trisakti Trisakti (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2020)
AbstractThis study wants to discuss the new aesthetic or queer aesthetic in the charm of makeup and costumes used in the film Asterix At The Olympic Games by director Frederick Forestier produced in 2008. The perspective taken in this study is charm through makeup and costumes, and its relevance to popular culture and people's interest in fantasy films. This study uses a qualitative method, with film studies as an approach in the analysis of cinematographic studies. Film studies in this study focus on social practice performances about the body, identity, representation, and elements contained in the charm of makeup and costumes in the film Asterix At The Olympic Games. The results showed that Asterix at The Olympic Games became a fantasy film genre that gave the complexity of the show as entertainment. In Asterix at The Olympic Games, there is a parody with an imitation of the situation and culture of Greece, which is conveyed through makeup, costumes, and performances. Alfred Gell, in his study of technology of enchantment, concerned the 'technical complexity' aspects of a work to attract the attention of the audience through the management of makeup and costumes. Furthermore, the concept of theatrical mimicry and parody as a 'technical complexity' is shown as a display of aesthetic queer for the sake of performance that can attract attention because of its shape as a popular culture product that is different for the audience.Keywords: new aesthetics; the enchantment of makeup and costumes; Asterix at the Olympic Games AbstrakPenelitian ini ingin membahas tentang estetika baru atau queer aesthetic dalam pesona make up dan kostum yang digunakan dalam film Asterix At The Olympic Games karya sutradara Frederick Forestier yang diproduksi tahun 2008. Sudut pandang yang diambil dalam penelitian ini adalah pesona melalui make up dan kostum, dan relevansinya terhadap budaya populer dan minat masyarakat terhadap film fantasi. Penelitian ini menggunakan metode kualitatif, dengan film studies sebagai pendekatan dalam analisis kajian sinematografinya. Film studies dalam penelitian ini berfokus pada pertunjukan praktik sosial mengenai ketubuhan, identitas, representasi, dan unsur-unsur yang terkandung dalam pesona make up dan kostum dalam film Asterix At The Olympic Games. Hasil penelitian menunjukkan Asterix at The Olympic Games menjadi genre film fantasi yang memberikan kompleksitas pertunjukan sebagai hiburan. Di dalam Asterix at The Olympic Games terdapat parodi dengan imitasi terhadap situasi dan budaya Yunani yang disampaikan melalui make up, kostum, dan pertunjukannya. Alfred Gell dalam telaahnya mengenai technology of enchantment mementingkan aspek ‘kerumitan teknik’ dalam suatu karya untuk menarik perhatian penonton melalui pengelolaan make up dan kostum. Lebih lanjut, konsep theatrical mimicry dan parodi sebagai suatu ‘kerumitan teknik’ ditunjukkan sebagai suatu display atas queer aesthetic untuk kepentingan pertunjukan yang mampu menarik perhatian karena bentuknya sebagai produk budaya populer yang berbeda bagi penonton.Kata kunci: estetika baru; pesona make up dan kostum; Asterix At The Olympic Games